Nigerian Immigrants and Xenophobic Violence in South Africa (2009)
The author argues that in many parts of Africa identity-politics and "nativist" narratives link migration to crime by making mobility a contentious political issue. This study exemplifies this by examining the experiences and adaptation of Nigerian migrants in South Africa and the confrontation with xenophobic violence this frequently involves. In South Africa, stereotypic reproduction represents the past in the present within the context of nation- building and contradictions of "African Renaissance "Despite the leading roles Nigeria and South Africa are playing in African politics and business, the xenophobia against African immigrants undermines the prospect of regional and continental development.